Reducing greenhouse energy consumption using novelty rooftop: a simulation - Harjunowibowo, Dewanto; Yate, Ding; Omer, Siddig A.; Riffat, Saffa B. (2017)
Recently, more than 80% of total energy of commercial greenhouse in the northern hemisphere is used just for heating. Mostly, the energy loss happens up to 40% caused by the poor U-value of the façades. Therefore, by lowering the U-value would decrease the energy consumption significantly. This simulation is conducted using EnergyPlus software to calculate the heat loss, heating demand and daylighting of a greenhouse with different envelope materials especially novelty rooftop. The orientation of buildings and its effect to electricity generated by semi-transparent PV double glazing are also discussed. In addition, the effect of the novel rooftop to daylighting inside the greenhouse is also investigated. The simulation shows that use materials with low U-value and novel rooftop could decrease the source energy consumption by 65% which is remarkable compared to commercial greenhouse. Besides, the best orientation for the PV module of the greenhouse in Nottingham, UK is facing west-south-east. While the indoor daylighting factor declined up to 65%. Therefore, using PVs with high efficiency would diminish the electricity losses and could be used for lighting energy alternative and others.